IN VITRO ANTIOXIDANT AND CYTOTOXIC ACTIVITY OF ISOLATED COMPOUNDS ON ROOTS OF CLERODENDRUM PHLOMIDIS LINN - M, Sathish; V, Niraimathi; KM, NOORULLA; A, Palanimuthu (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The main aim of the study was to screen the isolated compounds of Clerodendrum phlomidis roots for its in vitro antioxidant and anticancer activity and its efficacy against HeLa cell lines. Methods: Pet ether, chloroform, ethyl acetate and ethanol extracts was prepared and assayed for the presence of phytochemicals. Three compounds were isolated from ethanol extract of C. phlomidis by column chromatography such as ET1 (phenyl acetic acid), ET2 (ethyl-2-hydroxy- 4-methylbenzoate), ET3 (3,6,7-trihydroxy-2-(3-methoxyphenyl)-4H-chromen-4-one) characterized by IR (KBr), 1H-nuclear magnetic resonance (NMR), 13C-NMR and Gas chromatography–mass spectrometry. The above isolated compounds were subjected to in vitro antioxidant activity against 2,2-diphenylpicrylhydrazyl (DPPH) radical, superoxide radical scavenging assay and iron chelating activity. The effect of isolated compounds on HeLa cancer cell line was also evaluated by 3-(4,5-dimethylthiazol-2-Yl)-2,5-diphenyltetrazolium bromide colorimetric assay. Results: ET2 has good in vitro antioxidant activity against DPPH radical, super oxide radical and iron chelating activity with an inhibitory concentration 50% value of 360 μg/ml, 150 μg/ml and 130 μg/ml respectively. ET1 showed significant cytotoxic activity than the other two compounds on HeLa cells with a percentage cell growth of 21.9% and a growth inhibition of 50% value of 180 μg, respectively. Conclusion: On the basis of obtained results, ET1 and ET2 isolated from the ethanolic extract of C. phlomidis represent a new group of cytotoxic against HeLa cell line and antioxidant agents. Keywords: Column chromatography, Clerodendrum phlomidis, In vitro antioxidant activity, 2,2-diphenylpicrylhydrazyl, Cytotoxicity, 3-(4,5-dimethylthiazol-2-Yl)-2,5-diphenyltetrazolium bromide assay.